Startegi BUMDes dalam Meningkatkan Pendapatan Asli Desa di Desa Bentar Kecamatan Salem Kabupaten Brebes - Hilmawan Indra Mulyana; R.Rindu Garvera; Ii Sujai (Papsel Journal of Humanities and Policy, 2024)
This research is motivated by the non-optimal management of the Village Market in increasing Village Original Income by the Bentar Village Government, Salem District, Brebes Regency. The method used in this research is qualitative research method. Data collection techniques in this research include literature study, field study (observation and interviews) and documentation. The informants in this study were 7 people. The data analysis technique in this research is by condensing data, presenting data and drawing conclusions.       The method used in this research is descriptive analysis. Informants as many as 7 people. Data collection techniques are literature study, field study (observation and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so as to answer the problems in the study. The results showed that the Village Market Management strategy in Increasing Village Original Income in Bentar Village, Salem District, Brebes Regency has been running, but it is not optimal because problems are still found including: An incomplete organisational structure and limited facilities and infrastructure. Implementation that is not in accordance with planning and the absence of management training activities. No regular and programmed supervision and evaluation. Keywords: Strategy, Management, BUMDes, Village Original Revenue, Village Government